LITERATURE REVIEW ON DEVELOPING INDUSTRY IN ETHNIC MINORITY AND MOUTAINOUS AREAS - thi minh, khuyen pham; Thi Thu, Thuy Ha; Thi Mai, Yen Pham (International Journal of Research -GRANTHAALAYAH, 2020)
Ethnic minorities and mountainous areas, especially in developing countries, are often less developed than other regions. Although these areas have quite a lot of mineral resources, forest resources; harsh climates, difficult and inaccessible terrain, combined with political and social marginality certainly contribute to making difficulties in developing economies in general and industry in special. The article summarizes and analyzes previous studies on sustainable development in general, sustainable industrial development in ethnic minority and mountainous areas, in particular, to clarify which contents and issues have been studies and which contents need care for further studies, then a research model was proposed in line with the orientation of developing industry in ethnic minority and mountain areas sustainably.